2020
DOI: 10.1080/00380768.2020.1845972
|View full text |Cite
|
Sign up to set email alerts
|

Linking transport system of silicon with its accumulation in different plant species

Abstract: Silicon (Si) is a beneficial element for plants, which helps to mitigate various biotic and abiotic stresses. Since the last review on Si published in this journal in 2004, great progress has been made in understanding transport system of Si in different plant species. The discovery of two different transporters for Si (Lsi1 and Lsi2) in rice led to intensive investigation of Si transporters in other plant species. Lsi1 belongs to the Nodulin 26-like intrinsic proteins (NIPs) subfamily in the aquaporin (AQP) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 51 publications
(89 reference statements)
2
52
0
Order By: Relevance
“…To date, two different Si transporters, Lsi (channels) and Lsi2 (anion-type transporter) have been characterized in the roots of various plant species including rice, barley, maize, wheat, soybean, pumpkin, cucumber, tobacco, sorghum, tomato (for recent review see Mitani-Ueno and Ma, 2020 ), and recently date palm ( Phoenix dactylifera ) ( Bokor et al, 2019 ) and grapevine ( Noronha et al, 2020 ) have been added to the list. All these species differ greatly in ability to accumulate Si in upper plant parts.…”
Section: Essential and Beneficial Element Status Affects Silicon Uptake And Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, two different Si transporters, Lsi (channels) and Lsi2 (anion-type transporter) have been characterized in the roots of various plant species including rice, barley, maize, wheat, soybean, pumpkin, cucumber, tobacco, sorghum, tomato (for recent review see Mitani-Ueno and Ma, 2020 ), and recently date palm ( Phoenix dactylifera ) ( Bokor et al, 2019 ) and grapevine ( Noronha et al, 2020 ) have been added to the list. All these species differ greatly in ability to accumulate Si in upper plant parts.…”
Section: Essential and Beneficial Element Status Affects Silicon Uptake And Distributionmentioning
confidence: 99%
“…Increasing evidence suggests that nutritional status can affect Si accumulation and distribution in plants (e.g., Kim et al, 2014 ; Bokor et al, 2015 ; Hosseini et al, 2017 ; Wu et al, 2017 ; Chaiwong et al, 2020 ; Minden et al, 2020 ; Xiao et al, 2021 ). However, only a few studies have investigated the effect of specific nutrient imbalances on the expression of Si transporters and could be additionally affected by the Si concentration in the shoot ( Mitani-Ueno and Ma, 2020 ). It has been shown that limited supply of the macronutrients (N, P, K) and the micronutrient Fe, can induce Si accumulation in plant roots and/or shoots ( Wu et al, 2017 ; Chaiwong et al, 2018 , 2020 ; de Tombeur et al, 2020 ; Minden et al, 2020 ).…”
Section: Essential and Beneficial Element Status Affects Silicon Uptake And Distributionmentioning
confidence: 99%
“…Plants can accumulate from 0.1 to 10.0% Si in their tissues [ 12 , 13 ]. However, the absorption mechanisms differ between species, due to the presence of carrier proteins, which is reflected in a greater accumulation of Si in some plants, such as monocots [ 14 ]. Rice is considered a Si accumulator plant because the superior ability of roots to absorb Si from the soil, as compared to other plant species [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, plant roots are always exposed to some silicic acid (Si(OH) 4 ), which is the soluble form of silicates. Rice, barley, cucumber and tomato, among other plants, express silicon transporters in their roots (Mitani-Ueno and Ma, 2020). Concerted expression causes super saturation of silicic acid in the xylem sap (Sakurai et al, 2015) in wheat, rice, sorghum and other grasses (Casey et al, 2004; Mitani et al, 2005; Soukup et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous silica is the most readily dissolved form of silicate minerals (Schaller et al , 2021). Silicic acid molecules in the soil solution are available for plant root uptake through dedicated transporters (Mitani-Ueno and Ma, 2021). Their concerted expression causes super saturation of silicic acid in the xylem sap (Sakurai et al , 2015) of wheat, rice, sorghum and other grasses (Casey et al , 2004; Mitani et al , 2005; Soukup et al , 2020).…”
Section: Introductionmentioning
confidence: 99%